Amorphous-AlZnN/graphene heterostructure for solar-blind ultraviolet photovoltaic detectors. Issue 3 (1st February 2023) - Lin, Jun; Wang, Zhao; Lin, Xiuyu; Wei, Xuan; Zheng, Wei; Hu, Qichang
Abstract: Based on the characteristics of ultra-wide bandgap, radiation resistance, high thermal and chemical stability, AlN has been regarded as an ideal material with great potential for ultraviolet detectors. However, its application in solar-blind ultraviolet (SBUV) detection (between 200 nm and 280 nm) is limited by the absorption cutoff edge that is generally less than 200 nm. Here, a photovoltaic SBUV detector with p -Gr/ i -AlZnN/ n -Si heterojunction structure is first fabricated based on amorphous AlZnN film with an absorption cutoff edge of 258 nm, which is obtained by doping Zn atoms into AlN and controlling the proportion of Zn atoms. The device exhibits outstanding SBUV detection performance, such as the open-circuit voltage ( V oc ) reaching 0.87 V at 255 nm, a responsivity of 20.81 mA/W, an EQE of 10.13%, a detection rate of 3.98 × 10 12 Jones, a rise time of 33.2 ms and a fall time of 155 ms under 0 V bias. The results of this study indicate that amorphous AlZnN films applicable to SBUV detectors can be well prepared by energy band engineering, which also work as a reference for the preparation of AlZnN SBUV detectors with excellent performance.